Entering the 21st century : World development report, 1999/2000 summary - World Bank; World Bank (Washington, D.C. The International Bank for Reconstruction and Development/The World Bank, 2000)
This is a summary of the "Entering the 21st Century World Development Report, 1999/2000.
"World Bank 2000"--Cover.
rpm 07/02/2019
Ref
Keywords: Economic development; International trade; International finance; Investments, Foreign; Decentralization in government; Urbanization; Free trade; Economic indicators